The Fire Inside: Women Protesting AIDS in Prison since 1980. Issue 1 (March 2022) - Day, Emma
Abstract : In the late twentieth century, the American prison system expanded in ways that denied women, and especially working-class and women of color, adequate medical care with regard to HIV-AIDS and their reproductive, chronic, and other illnesses. The experience of living within a racist, misogynistic, and privatized prison system shaped women's organizing on the inside, inspiring forms of mutual aid among prisoners and compelling the formation of inside–outside alliances. Activists not only addressed HIV-AIDS, but also the absence of all the healthcare that incarcerated women failed to receive. Their efforts highlight the systemic and cyclical problems diverse groups of women have faced within the HIV-AIDS epidemic in the United States, as well as women's interpersonal, organizational, and legal efforts to overcome them.